2007
DOI: 10.1002/bit.21292
|View full text |Cite
|
Sign up to set email alerts
|

The stability of engineered thermostable neutral proteases from Bacillus stearothermophilus in organic solvents and detergents

Abstract: Engineered extremely thermostable variants of the thermolysin-like protease from Bacillus stearothermophilus possessing an introduced disulfide bond G8C/N60C (double mutant, DM) and six additional amino acid substitutions in the exposed loop region 56-69 (Boilysin, BLN) have been probed with respect to stability toward water-miscible organic solvents and detergents. The solvent concentrations where 50% of enzyme activity were irreversibly lost (C(50)) decreased in the order methanol > 2-propanol > dimethylsulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The maintenance of protein conformation over a wide concentration range of water-miscible organic solvents has been reported in other enzymes, such as thermolysin [79] and neutral protease [80]. Organic-solvent-tolerant enzymes appear to be quite attractive for industrial applications, such as bioremediation of the organic solvent-contaminated samples.…”
Section: Discussionmentioning
confidence: 98%
“…The maintenance of protein conformation over a wide concentration range of water-miscible organic solvents has been reported in other enzymes, such as thermolysin [79] and neutral protease [80]. Organic-solvent-tolerant enzymes appear to be quite attractive for industrial applications, such as bioremediation of the organic solvent-contaminated samples.…”
Section: Discussionmentioning
confidence: 98%
“…FAGLA and ZDFM are substrates routinely used in the characterization of thermolysin 3,14) and neutral proteases from Bacillus stearothermophilus. [37][38][39] FAGLA is a poorly soluble neutral dipeptide, while ZDFM is a negatively charged dipeptide. We have reported several thermolysin variants, L144S, D150E, and I168A, with higher FAGLA-and ZDFM-hydrolyzing activities than WT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this stability is interesting between 37˚C -40˚C. Above 50˚C, this enzyme is still stable with a clear decrease in activity despite the fact that the bacteria no longer grow at these temperatures in contrary to studies previously demonstrated [12] [13]. Indeed, the in vitro analysis conditions do not necessarily reflect the physiological conditions in vivo and that environmental factors can positively or negatively influence the protein stability that can explain this result [14].…”
Section: Discussionmentioning
confidence: 77%